2010
DOI: 10.1094/phyto-02-10-0044
|View full text |Cite
|
Sign up to set email alerts
|

Cpkk1, MAPKK of Cryphonectria parasitica, Is Necessary for Virulence on Chestnut

Abstract: The role of Cpkk1, a mitogen-activated protein kinase from Cryphonectria parasitica, was investigated by generating a number of mutant strains that overexpress, under the control of the cryparin promoter, both the wild-type protein and its allele with an extensive deletion in the catalytic domain. Furthermore, a hairpin construct was built and expressed to cause specific silencing of Cpkk1 mRNA transcripts. Specific mRNA silencing or overexpression was confirmed on both Northern and Western blot analysis. Sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The functions of Slt2 MAPK cascade in virulence have also been characterized in several plant pathogens. Silencing of Cpkk1 (a MAPKK) in Cryphonectria parasitica correlated with a marked reduction in virulence on 3-year-old chestnut trees (Rostagno et al, 2010). In C. lagenarium, Maf1 is required for the early differentiation phase of appressorium formation because mutants failed to form appressoria (Kojima et al, 2002).…”
Section: Function Of Fgmkk1 In F Graminearum 2031mentioning
confidence: 99%
“…The functions of Slt2 MAPK cascade in virulence have also been characterized in several plant pathogens. Silencing of Cpkk1 (a MAPKK) in Cryphonectria parasitica correlated with a marked reduction in virulence on 3-year-old chestnut trees (Rostagno et al, 2010). In C. lagenarium, Maf1 is required for the early differentiation phase of appressorium formation because mutants failed to form appressoria (Kojima et al, 2002).…”
Section: Function Of Fgmkk1 In F Graminearum 2031mentioning
confidence: 99%
“…In contrast, no elements of the cell integrity pathway have been investigated so far in C. parasitica , except Cpkk1, whose function was recently revealed in our laboratory using silencing techniques (Rostagno et al ., ). Experiments demonstrated that Cpkk1 plays an important role in conidiation, growth on minimal medium and virulence.…”
Section: Discussionmentioning
confidence: 97%
“…Virulence assays were performed on stems of European chestnut tree ( Castanea sativa ) with four replicates per fungal strain as described previously (Rostagno et al ., ). Inoculated stems were kept at 24 °C under normal light covered with plastic bags to maintain moisture.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Relevant to our findings, previous studies have suggested that signal transduction components may be perturbed by hypovirus infection to induce hypovirulence (Turina and Rostagno, 2007 ). Several of these genes constitute the G-protein signaling cascades while others function in mitogen-activated protein kinase (MAPK) pathways (Rostagno et al, 2010 ). MAPKs of Ser/Thr kinases have been shown to be required for fungal growth, development, and pathogenicity (Park et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%